Assessing the applicability of forensic analysis of windicators for Typhoon Haima (Lawin) - Dacanay, John Paul T.; Hernandez, Jaime Y. Jr.; Agar, Joshua C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Typhoons are one of the biggest causes of strucural failure in the Philippines. Typhoon Lawin was a typhoon that struck the Northern Luzon on October 19, 2016. Through a field survey two weeks after the typhoon's passage, two windicators, simple structures that failed due to the force of the wind, were chosen to determine the wind speeds that caused the damage to. Given the physical and mechanical properties of the windicators, a CAD model was made and computational fluid dynamics and structural analysis were applied to determine the wind speeds. The two windicators estimate 202 kph and 221 kph 10-min sustained winds with gusts up to 336 kph and 367 kph. Using the Pressure data from multiple stations, pressure and velocity models were made using Holland's equation. The 12AM (PST) Oct 19 model applicable to the time it passed through the study area predicted maximum gusts of 382 kph. Using testimonies from people, the cubic spline interpolated storm track was validated through conforming a calmness felt in the area, signifying the presence of an eye. Using the Enhanced Fujita Scale, gusts experienced at the area range from 190 kph to 240 kph. However, both windicators' time of failure could not be determined due to their close proximity to the typhoon track. Therefore, the wind-speed obtained from both windicators cannot be plotted onto the radial velocity profile of the typhoon. The study found that determining Typhoon Lawin's location when the windicator failed is important attribute of windicators in order to be useful in forensic analysis to determine the maximum wind speeds of a typhoon.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Winds -- Speed -- Measurement